2018
DOI: 10.1002/biof.1460
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in serum concentrations of FGF19, FGF21, and FGF23 in patients with urothelial carcinoma

Abstract: Fibroblast growth factors (FGF) 19, 21, and 23 have been reported as functional factors in human metabolic diseases and malignancies. We performed a prospective survey to compare circulating FGF levels in urothelial carcinoma (UC) patients and normal controls. Between 2016 and 2017, 39 patients with UC of the urinary bladder or upper urinary tract who received surgical intervention were included. All the serum samples were obtained before surgeries. The control group included 28 healthy volunteers. Analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…However, reports have been published on a correlation between increased leptin levels and increased serum concentrations of FGF23. Considering the fact that increased body mass, dyslipidemia, and increased leptin levels are factors involved in the pathogenesis of endometrial cancer, one should expect that patients with endometrial cancer should also present with higher levels of FGF23 [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, reports have been published on a correlation between increased leptin levels and increased serum concentrations of FGF23. Considering the fact that increased body mass, dyslipidemia, and increased leptin levels are factors involved in the pathogenesis of endometrial cancer, one should expect that patients with endometrial cancer should also present with higher levels of FGF23 [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…10 Since cancers often coexist with systemic metabolic disorders, there is growing awareness that FGF21 may also be related to carcinogenesis or cancer prognosis. Up to date, in a few population-based studies with small sample sizes, elevated circulating FGF21 levels were consistently related to increased human cancer risk, including breast cancer, 11 clear cell renal cell carcinoma (ccRCC), 12 colorectal cancer, 13,14 urothelial carcinoma, 15 gastric cancer, 16 thyroid cancer 17 We are aware of only one prior epidemiology study concerning the association between serum FGF21 levels and cancer survival (ccRCC). 12 In that small cohort study involving 98 ccRCC patients and 51 healthy controls, serum FGF21 seemed to increase since the earliest stages of the disease, patients with ccRCC had significantly higher levels of serum FGF21 compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…5 Increasing evidences showed that circulating FGF21 levels were generally associated with metabolic disorder diseases, such as obesity, 6 diabetes, 7 hypertension, 8 dyslipidemia 9 and NAFLD. 10 Since metabolic disorder diseases are important pathogenic factors for many cancers, and cancers often coexist with systemic metabolic disorder, several studies have consistently reported increased circulating FGF21 levels in various human cancers, including breast cancer, 11 clear cell renal cell carcinoma (ccRCC), 12 colorectal cancer, 13,14 urothelial carcinoma, 15 gastric cancer, 16 thyroid cancer 17 and endometrial cancer. 18 To date, although the exact mechanisms linking FGF21 and carcinogenesis or cancer prognosis are scarce, it was suggested that at least circulating FGF21 may serve as a potential diagnostic as well as a prognostic biomarker for patients with certain cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Rare forms of colon adenocarcinoma are characterized by FGF23 secretion with hypophosphatemia [ 67 ] whereas in other forms, plasma FGF23 is increased [ 60 ]. In urothelial cancer, FGF23 is also elevated [ 71 ]. Further malignancies found to exhibit, at least in part, higher FGF23 levels are ovarian cancer [ 101 ], prostate cancer [ 42 ], and multiple myeloma [ 99 ].…”
Section: Pathophysiological Roles Of Fgf23mentioning
confidence: 99%